2022
DOI: 10.31586/ojer.2022.200
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism and Self-Esteem as Correlates of Secondary School Students’ Mathematics Academic Achievement in Anambra State

Abstract: The impact of narcissism and self-esteem on academic achievement has long been an important issue in developmental research. The study aimed to explore the students' narcissism and self-esteem as correlates of academic achievement in Mathematics in Anambra State. Five research questions and five null hypotheses guided the study. The study adopted a correlational approach. The population of the study comprised of 21204 SS2 students from which a sample of 630 was drawn. Multi-stage procedure was used to select t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
(23 reference statements)
5
3
0
Order By: Relevance
“…This implies that self-worth and critical thinking skill have certain level of influence on students' academic achievement scores in mathematics. The findings partially supported the study of Anyanwu et al (2022) which recorded that self-worth positively contributed in predicting the regression model while mental toughness negatively contributed in predicting the regression model.…”
Section: Discussion Of Findingssupporting
confidence: 85%
See 2 more Smart Citations
“…This implies that self-worth and critical thinking skill have certain level of influence on students' academic achievement scores in mathematics. The findings partially supported the study of Anyanwu et al (2022) which recorded that self-worth positively contributed in predicting the regression model while mental toughness negatively contributed in predicting the regression model.…”
Section: Discussion Of Findingssupporting
confidence: 85%
“…This is an indication that the mental toughness, self-worth and critical thinking are potentially fit to examine students' motivational propensity to respond and achieve academically. This supported the findings from the study of Anyanwu, Ezenwosu and Emesi (2022) which recorded that the seven assumptions that were tested in the study which involved mental toughness, self-worth and narcissism were statistically fit for their study. Meeting the assumptions of the regression model implies that the data are suitable and amenable for the analysis.…”
Section: Discussion Of Findingssupporting
confidence: 79%
See 1 more Smart Citation
“…In Anyanwu and Emesi's study, the dimensions of achievement goal orientation were positively and significantly related with academic achievement. In another study, Anyanwu and Emesi (2021) revealed a very low negative relationship between students' academic self-concept and their academic achievement in English language. The study of Emesi, Anyanwu and Ezenwosu (2022) revealed that clusters of achievement goal orientation were among the variables that relatively and jointly predicted students' academic achievement in English language.…”
mentioning
confidence: 92%
“…In the study of Anyanwu and Emesi (2020) it was indicated that mastery-approach, masteryavoidance and performance-approach were low positively related to academic achievement, but performance-avoidance and work-avoidance were very low positively related to academic achievement. In Anyanwu and Emesi's study, the dimensions of achievement goal orientation were positively and significantly related with academic achievement.…”
mentioning
confidence: 97%